EVIDENCE FROM OPHIOLITES, BLUESCHISTS, AND ULTRAHIGH-PRESSURE METAMORPHIC TERRANES THAT THE MODERN EPISODE OF SUBDUCTION TECTONICS BEGAN IN NEOPROTEROZOIC TIME - Stern R.J. (My University, 2005)
Earth is the only known planet with subduction zones and plate tectonics, and this fact demonstrates that special conditions are required for this mode of planetary heat loss. Sinking of cold, dense lithosphere in subduction zones is the principal plate-driving force, so plate tectonics could not have begun until Earth cooled sufficiently to allow lithosphere to collapse into the underlying asthenosphere. Direct geologic evidence for when the mod- ern episode of subduction tectonics began focuses on the first appearance of ophiolitic graveyards, blueschist facies metamorphic rocks, and ultrahigh-pressure metamorphic ter- ranes. Ophiolites manifest two modes of lithospheric motion expected from subduction tectonics: seafloor spreading and obduction. High-pressure, low-temperature metamorphic blueschists and ultrahigh-pressure terranes indicate subduction and exhumation of oceanic and continental crust, respectively. These lines of evidence indicate that the modern style of subduction tectonics began in Neoproterozoic time. This revolution in the functioning of the solid Earth may have driven wild fluctuations in Earth's climate, described under the ''snowball Earth'' hypothesis. These conclusions may be controversial, but suggest fruitful avenues for research in geodynamics and paleoclimate.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic